GEOTECHNICS STUDY FOR DESIGN OF OPEN PIT SLOPES AT COAL MINING SITE PLAN, SAROLANGUN, JAMBI - -, Geni Dipatunggoro; -, Zufialdi Zakaria; -, Irvan Sophian (Bulletin of Scientific Contribution, 2011)
Site plan of coal mining at Sorolangun, Jambi, is required geotechnical study for cut slope design. Mining plan. In open pit plan, to take stable slope, is required slope mass rating (SMR). SMR method is requiring rock mass rating value. According to soil and weak-rock mass properties of Muaraenim Formation, stable